Influence of Summer Sublimation on δD, δ18O, and δ17O in Precipitation, East Antarctica, and Implications for Climate Reconstruction From Ice Cores. Issue 13 (1st July 2019) - Pang, Hongxi; Hou, Shugui; Landais, Amaelle; Masson‐Delmotte, Valérie; Jouzel, Jean; Steen‐Larsen, Hans Christian; Risi, Camille; Zhang, Wangbin; Wu, Shuangye; Li, Yuansheng; An, Chunlei; Wang, Yetang; et al.
Abstract: In central Antarctica, where accumulation rates are very low, summer sublimation of surface snow is a key element of the surface mass balance, but its fingerprint in isotopic composition of water (δD, δ 18 O, and δ 17 O) remains unclear. In this study, we examined the influence of summer sublimation on δD, δ 18 O, and δ 17 O in precipitation using data sets of isotopic composition of precipitation at various sites on the inland East Antarctica. We found unexpectedly low δ 18 O values in the summer precipitation, decoupled from surface air temperatures. This feature can be explained by the combined effects of weak or nonexistent temperature inversion and moisture recycling associated with sublimation‐condensation processes in summer. Isotopic fractionation during the moisture‐recycling process also explains the observed high values of d‐excess and 17 O‐excess in summer precipitation. Our results suggest that the local cycle of sublimation‐condensation in summer is an important process for the isotopic composition of surface snow, water vapor, and consequently precipitation on inland East Antarctica. Key Points: Isotopic composition in summer precipitation on inland East Antarctica is more depleted than expected from the range of surface air temperatures during precipitation The strong depletion of isotopic composition in summer precipitation are caused by the combined effects of weak or nonexistent temperature inversion and moisture recycling associated with snow sublimation Isotopic fractionation occurs during the moisture recycling process